Peningkatan Produktivitas Dan Kreatifitas Kelompok Pengelola Bank Sampah - Nuril Lutvi Azizah; Cindy Cahyaning Astuti; Metatia Intan Mauliana (IAI Darussalam, 2020)
Pogar is a village located in Bangil District, Pasuruan Regency. The majority of the people earns as farmers and small home indutsries. The most commonly found anorganic rubbish is plastic, found around 400 kg per month in this village. The plastic waste can be recycled to be diverse. However, there are a number of things that have become partners' problems, which are not insufficient capital for the purchase of equipment, increasing community creativity through related activities, and the supply of garbage must always be large and in constant amounts. Regarding the main problem described, this program will offer solutions that are expected to help reduce the problems faced by partners. The method that will be used in addition to Socialization or Counseling so that the community is more creative and productive as well as the procurement of equipment and goods that can support partners in processing waste recycling into valuable products. We also market their products through the internet and provide tutorials on making samples of products online or offline. The result of the services is that groups can create creative products and utilize anorganic waste around their environment, as well as market the products they have produced.